Corn-Expressed Phytase Influence on Broiler Growth Performance - Majeed, S.; Nusairat, B.; Joardar, D.; Qudsieh , R.I.; Edens, F.; Broomhead, J.; Lanahan, M.; Brake, J. (International Journal of Poultry Science, 2020)
Background and Objective: Formulating a balanced diet that would provide the required nutrients is very important for achieving optimal broiler growth. This study was conducted to determine the optimal calcium to available phosphorus ratio (Ca:AvPi) for feed with or without corn-expressed phytase (CEP) addition. Materials and Methods: A 35d trial was conducted to determine growth performance, effects of either decreasing Ca:AvPi ratio as bird ages, without CEP, or increasing Ca matrix credit when feeding CEP. A total of 1152 one-day-old male broilers were assigned to 6 dietary treatments (Diets A to F) with 16 birds per pen and 12 replicate pens per treatment. Diets A and B didn’t contain CEP and had 0.5 and 0.45% AvPi in the starter (0-15 day) and grower (16-35 day) feeds, respectively. Diet A had a decreasing Ca:AvPi from 2:1 in starter to 1.85:1 in grower, whereas Ca:AvPi of diet B was constant at 2:1 for both phases. Remaining diets contained 3000 FTU kg–1 of CEP. Diet C contained CEP added on top. Diets D to F had 0.12% lower AvPi while Ca was reduced by 0.11, 0.15 or 0.17%, respectively. Results: No differences in growth performance (p>0.05) were observed between birds fed diets A or B. In general, birds fed CEP had higher early (0-15 and 16-28 day) and overall body weight (BW), body weight gain (BWG) and feed intake (FI) compared to those fed diet A or B (p<0.05). Overall (0-35 day) feed conversion ratio (FCR) was improved for all CEP-supplemented diets compared to Diet A. Assigning different Ca matrix values among CEP treatments had no effect (p>0.05) on growth performance of broilers. Overall FCRs (0-35 day) with all CEP-supplemented diets were better than that of the unsupplemented diet A. Conclusion: Results demonstrated that adding CEP improved growth performance and reducing Ca:AvPi ratio as the bird aged did not affect performance for diets without CEP. In addition, with a 0.12% AvPi matrix value, adjusting Ca matrix values between 0.11 and 0.17% did not have a large effect on animal performance when diets included 3000 FTU kg–1 CEP.